Stakeholders’ Consultation Meeting on Agrifood value chains in Odisha-Challenges and Opportunities Video - Mitra, Archisman; Breisinger, Clemens; Pauw, Karl; Kirui, Leonard; Kadian, Mohinder; Kassim, Yumna (CGIAR, 2023)
This video was recording at the Stakeholders’ Consultation Meeting on Agrifood value chains in Odisha-Challenges and Opportunities held last Nov. 29, 2023. This seminar was co-organized by Agriculture Consultancy Support Service Cell (ACSSC), OUAT, IFPRI, and the CGIAR Research Initiative on National Policies and Strategies. The views and opinions expressed in this video are those of the speakers(s) and are not necessarily representative of or endorsed by CGIAR, IFPRI, and OUAT.